Formulation and in vitro Evaluation of Betahistine Dihydrochloride Twice Daily Controlled Release Matrix Tablet - Islam, Asraful; Halder, Shimul; Bachar, Sitesh Chandra (Dhaka University Journal of Pharmaceutical Sciences, 2012)
In order to reduce dosing frequency, a sustained release dosage form of betahistine dihydrochloride was developed as a twice daily controlled release tablet formulation that could be used to decrease vertigo resulted in Meniere's disease for a prolonged time. Six formulations were developed by using Methocel K4M CR, Methocel K15M CR and Methocel K 100 LVCR as single and combinations in different percentage. The tablets were prepared by wet granulation method. Physical properties of betahistine dihydrochloride granules and betahistine dihydrochloride matrix tablets were evaluated. The tablets were characterized for Betahistine Dihydrochloride release in both gastric simulated fluid (0.1 N HCl, pH 1.3) and simulated intestinal fluid (buffer solution pH 6.8). The data were subjected to different models in order to evaluate their release kinetics and mechanisms. The results of the in vitro dissolution study indicate that most of the formulations showed above 80% of drug release in 12 hours but formulations (F-2 and F-4) met the official specification of release profile. Dissolution data were fitted to zero order equation, Higuchi square root law, Korsmeyer-Peppas model and Hixson-Crowell cube root law as these plots showed the highest value of linearity to evaluate kinetic data. The release of betahistine dihydrochloride was prolonged for 12 hours indicating the usefulness of the formulations for twice daily dosage forms, leading to improve efficacy, controlling the release and better patient compliance. DOI: http://dx.doi.org/10.3329/dujps.v10i2.11786 Dhaka Univ. J. Pharm. Sci. 10(2): 93-100, 2011 (December)